2017
DOI: 10.1055/s-0036-1572493
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Glenoid Fossa Fracture, Progressive Ankylosis, Total Joint Reconstruction with Alloplastic Prosthesis to Normalized Function Including Evaluation with F18-PET/CT–a Four Year Follow-up

Abstract: Temporomandibular joint replacement (TJR) with alloplastic prosthesis has shown promising long-term results in end stage joint disorders. We present a case of young woman with painful ankylosis that where reconstructed with TJR, due to a complex mandibular fracture with dislocation of the left condyle into the middle cranial fossa two years earlier. At the age of 18 the subject underwent a total joint replacement with custom-made alloplastic TMJ prosthesis. To determine the bone response and remodeling activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Only two of them (Rikhotso and Bobat in 2016 and Lindell and Thor in 2017) were reconstructed using a TMJ prothesis, and both were total alloplastic reconstruction, using a condyle and glenoyd fossa prosthesis with good results in a long term follow up. Our case is the first to use a partial TMJ prosthesis, reconstructing only the glenoid fossa and maintaining the condyle that had not been fractured, with good results in a follow up of 12 months 10,11 .…”
Section: Discussionmentioning
confidence: 81%
“…Only two of them (Rikhotso and Bobat in 2016 and Lindell and Thor in 2017) were reconstructed using a TMJ prothesis, and both were total alloplastic reconstruction, using a condyle and glenoyd fossa prosthesis with good results in a long term follow up. Our case is the first to use a partial TMJ prosthesis, reconstructing only the glenoid fossa and maintaining the condyle that had not been fractured, with good results in a follow up of 12 months 10,11 .…”
Section: Discussionmentioning
confidence: 81%
“…The selection of a reconstruction material should be based on the age of the patient, time elapsed between initial injury and treatment, and size of the defect. TMJ prostheses are becoming increasingly popular, and they were applied in four cases included in this review [72,76,90,93]. A recent systematic review concluded that TMJ prostheses are reserved for patients presenting with persistent pain, bony or fibrous ankylosis, or osteomyelitis after the primary closed or open treatment of mandibular condyle fractures [125].…”
Section: Etiology and Treatment Of Intracranial Dislocation Of The Co...mentioning
confidence: 99%